(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To compare clinical characteristics and related factors of dermatophyte finger nail infection and yeast finger nail infection. Research subjects and methods: Cross-sectional descriptive study based on data of 209 patients diagnosed with fungal fingernail infection by clinical examination and either KOH examination or fungal culture at the National Hospital of Dermatology & Venereology (NHDV) from August 2018 to August 2019. Results: Among 209 patients with fungal nail infection, 76 patients (36.4%) infected with dermatophytes and 133 patients (63.6%) infected with yeast. Dermatophyte nail infection was more common in men than women (63.2% vs 36.8%), whereas yeast nail infection was more common in women than men (59.4% vs 40.6%). Compared to patients infected with dermatophytes, those infected with yeast exposed to water and chemicals more frequently (76.7% vs 50%), experienced more pain (33.1% vs 12.0%) and had higher proportion of thumber nail damage (85% vs 50%). Patients infected with dermatophytes suffered from frequent pressure on the nail more often than those infected with yeast (13.2% versus 4.5%). The most common clinical symptoms in the yeast group was nail separation (67.1%), in the filamentous fungus group was nail thickening (67.7%). Paronychia is more common in the yeast group than in the dermatophyte group (38% vs 18,6%), whereas subungual keratosis, nail thickening, and cracking are more common in dermatophyte than in yeast group. The damage of the lateral and the distal nail margin was more common in the dermatophyte group than in the yeast group (88.6% vs 70.4%). The damage to the proximal nail margin was more common in the yeast group than in the dermatophyte group (29.6% vs 11.4%). Conclusion: There are clinical differences and some related factors in the 2 groups of patients with fungal finger nail infections caused by dermatophyte and yeast. This difference would be useful for doctors to predict the causative fungal strain, especially when there is no paraclinical support.